El comportamiento de los verbos haber y ser en función de auxiliar de los tiempos compuestos (siglos XIII-XVII) - Idrisz, Ágnes (Acta Hispanica, 2009)
In the old Spanish language the usage of the compound tenses formed with the auxiliary ’haber’ and the participle form shows several differences compared to today’s usage. It turns out from fragments from the XIII-XVII. centuries that the word order of the elements in the structure was not bound: on the one hand, the participle form could come before the auxiliary, on the other hand, other parts of the sentence could be inserted between the two elements of the structure. Furthermore, the participle form could possibly be reconciled with the direct object of the sentence. The above mentioned features can be found in the earliest fragments of the ’corpus’ on a larger scale, whereas by the XVII. century – due to the grammatical progress of the structure – these features had almost completely disappeared. Another peculiarity about the development of the structure haber + participio pasado is that the occurence of the above mentioned features depended largely on the genre of the text. There is a whole range of studies available which deal with the emergence and the forms of the compound tenses. Therefore, the purpose of the present study is to examine – based on the article of Concepción Company in 1983 – how much these compound tenses are present in the texts from different ages, as well as how much the frequency of their presence was influenced by the genre of the texts.